Caracterização morfomolecular e interação parasito-hospedeiro de Myxozoa Grassé, 1970 (Cnidaria: Myxosporea) infectando peixes brasileiros - Araujo, Rafaela Franco de (2024)
Fish are among the vertebrates most susceptible to parasitic infection, due to their environment, where water facilitates the transmission and dispersion of these organisms. Some species of myxozoans are highly pathogenic, as they cause serious damage to their hosts (farmed and wild fish) and great economic losses to the fishing industry worldwide. Thus, the objectives of this thesis were: a) to document the occurrence and geographic distribution of ichthyoparasites of the Myxozoa Class in farmed and wild teleost fish populations in Brazil, in addition to describing the parasite-host interaction, infection sites and the main histopathological alterations caused to the fish. The systematic review study located 226 articles dealing with myxozoan parasites infecting fish in Brazil and provided a broad overview of relevant information that can contribute to strategies and actions for the economic development of aquaculture and for the conservation of biodiversity in Brazil. In addition, it highlighted the concentration of publications in some regions of the country to the detriment of others. In this sense, it is suggested to strategically expand research in areas where there is a high diversity of host fish and where there is a deficit or absence of studies on myxozoans in fish, which may lead to the discovery of new species; b) describe a new species of Ceratomyxa infecting the gallbladder of Pterophyllum scalare from the municipalities of Tartarugalzinho and Macapá, in the Amazon region of Brazil. Phylogenetic analysis showed that the new species is grouped in the family Ceratomyxidae, in addition to being positioned in the same subclade of freshwater ceratomyxids from the Brazilian Amazon, demonstrating that this species shares a common ancestor with its close relatives, based on geographic affinity. This is the first description of Myxozoa in P. scalare and the thirteenth Ceratomyxa in Brazil or South America, contributing to the knowledge of the biodiversity of the Amazon region; c) evaluate the hematological parameters of Metynnis lippincottianus from the Curiaú River, in the municipality of Macapá-AP. In this sense, Metynnis lippincottianus presented a hematological profile with interspecific variations, similar to wild fish species.